The roles of cues for assessing consumers perceived quality at the destination level - Hossain, Enayet; Quaddus, Mohammed; Haque, A. K. M. Ahasanul (TextRoad Publication, 2013)
This study is conducted in exploring the relationship between intrinsic and extrinsic cues, and quality at the destination level of Cox’s Bazar in Bangladesh. A sample of 602 was used to identify relationships between cues and quality. Perceived intrinsic cue has been considered as formative construct whereas extrinsic cues are considered as reflective constructs. Partial Least Square (PLS) based Structure Equation Modeling (SEM)analysis reveals that both cues have positive impacts on perceived quality. The principle guideline of this study is to support destination operators in tourism planning and development. It will assist for successful business operation and long -term sustainability of the tourism destination. Theoretically, this study contributes to enhancing the causal relationship s between cues and quality which have yet to be included in the tourism literature. Limitations of the study are discussed including future research direction.